1986
DOI: 10.1002/aic.690320808
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of drying for hygroscopic porous media

Abstract: A mathematical model is developed to simulate the drying of hygroscopic porous media and, in particular, of wood. Drying rate experiments were performed using wood specimens and a nonhygroscopic porous ceramic solid and were simulated using the appropriate version of the drying model. Calculated model predictions are in very satisfactory agreement with experimental results. An examination of the relative impacts on drying of the transport mechanisms that comprise the model leads to meaningful interpretations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(101 citation statements)
references
References 7 publications
5
94
0
2
Order By: Relevance
“…In contrast to that, drying of hygroscopic materials not only involves free and capillarity water but also a tightly bound water that strongly attach to the solid matrix up to hydration temperature [1]. Previous studies on drying of hygroscopic and nonhygroscopic have present different equations and formulations as well as the concept that had been derived [1,2,3,4,5]. Bound water movement is expressed in terms of the diffusion of sorbed water driven by a gradient in the chemical potential of the sorbed water molecules [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to that, drying of hygroscopic materials not only involves free and capillarity water but also a tightly bound water that strongly attach to the solid matrix up to hydration temperature [1]. Previous studies on drying of hygroscopic and nonhygroscopic have present different equations and formulations as well as the concept that had been derived [1,2,3,4,5]. Bound water movement is expressed in terms of the diffusion of sorbed water driven by a gradient in the chemical potential of the sorbed water molecules [2].…”
Section: Introductionmentioning
confidence: 99%
“…During low moisture contents, pores mainly consist of bound water and vapour. Stanish et al [3] in their development had derived a uniquely explicit expression for boundwater flux in terms of temperature and vapor pressure gradients. Meanwhile, Zhang et al [4] and Haghi [5] revealed that the bound water transport mechanism only effective when saturation irreducible is reached.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal behaviour of biomass is strongly dependent upon the biochemical composition and structure of the feedstock, and the specific effects of MW heating on biomass has been previously explored [192][193][194]. Within the biomass, not all of the biochemical constituents are able to absorb MWs, and even if they can absorb MWs, the degree of polarisation [183,[195][196][197]. The bulk heating mechanism of microwave irradiation causes water to vaporise within the pores of the biomass, as water dipoles attempt to continuously reorient within the oscillating electric field.…”
Section: Understanding Selective Heating Behaviourmentioning
confidence: 99%
“…Several workers have investigated the detailed modelling of moisture transport through porous media containing a gas phase, [19,49,52], but two limiting cases may be identified [34]. In the dry shell model, the vapour space is in the shell itself and an evaporative front recedes through the droplet.…”
Section: Shell Formationmentioning
confidence: 99%